The importance of port logistics on the cost of transport and stowage at ports - Bernal Valverde P. (Feed manufacturing in Southern Europe: New challenges, 1997)
The author describes the Port of Tarragona, mainly in the field of cereal and by-products traffic and their volume in the past years. He explains the factors which determine the harbour evolution and the costs of transport for supplying raw materials to feed manufacturers and the harbour, storage and distribution costs. The transport cost by road and by railroad are also explained.
South European Feed Manufacturers Conference, 1996/05/09-11, Reus (Spain)